Answer:
x - 3 < -5 is the inequality x < -2 is the solution
Step-by-step explanation:
x - 3 < -5
add 3
x < -2
Answer:
1. a/2b 2. 5/6 3. x-1/2 4. y-5/y+5 5. x+5/x-1
Step-by-step explanation:
Answer:
The zeros are : 0, 3, -6, 7.
Step-by-step explanation:
Zeros of a polynomial is the values at which the polynomial becomes zero. They are also called the roots of the polynomial.
When (x - a)(x - b) = 0, we can say that either (x - a) = 0 or (x - b) = 0. At least one zero renders the whole equation to be zero.
Now, we are given that: x. (x - 3). (x + 6). (x - 7) = 0
⇒ To make the equation zero, at least one of the following should be true:
x = 0
x - 3 = 0 ⇒ x = 3
x + 6 = 0 ⇒ x = -6
x - 7 = 0 ⇒ x = 7
Therefore, x can take any one of the above values and that would make the polynomial zero.
Answer:
Below
Step-by-step explanation:
Substituting the given values:
f(6) = 6(2/3) - 2 = cube root of 6^2 - 2 = cube root 36 - 2
f(-6)= (-6)(2/3) - 2 = cube root of(-6)^2 - 2 = cube root 36 - 2
So This is true,
f(6) = cube root of 6^2 - 2 = cube root 36 - 2 = 1.3019
2 * f(3) = 2 * (cube root of 3^2 - 2 ) = 2 * (cube root of 9 - 2) = 0.1602
So False,
3.84 meters because 2% of 48 is 0.96, 0.96*4, which is 3.84